Acute treatment with relaxin protects the kidney against ischaemia/reperfusion injury. Issue 11 (20th September 2013) - Collino, Massimo; Rogazzo, Mara; Pini, Alessandro; Benetti, Elisa; Rosa, Arianna Carolina; Chiazza, Fausto; Fantozzi, Roberto; Bani, Daniele; Masini, Emanuela
Abstract Although recent preclinical and clinical studies have demonstrated that recombinant human relaxin (rhRLX) may have important therapeutic potential in acute heart failure and chronic kidney diseases, the effects of acute rhRLX administration against renal ischaemia/reperfusion (I/R) injury have never been investigated. Using a rat model of 1‐hr bilateral renal artery occlusion followed by 6‐hr reperfusion, we investigated the effects of rhRLX (5 μg/Kg i.v.) given both at the beginning and after 3 hrs of reperfusion. Acute rhRLX administration attenuated the functional renal injury (increase in serum urea and creatinine), glomerular dysfunction (decrease in creatinine clearance) and tubular dysfunction (increase in urinary excretion of N‐acetyl‐β‐glucosaminidase) evoked by renal I/R. These beneficial effects were accompanied by a significant reduction in local lipid peroxidation, free radical‐induced DNA damage and increase in the expression/activity of the endogenous antioxidant enzymes Mn‐ and CuZn‐superoxide dismutases (SOD). Furthermore, rhRLX administration attenuated the increase in leucocyte activation, as suggested by inhibition of myeloperoxidase activity, intercellular‐adhesion‐molecule‐1 expression, interleukin (IL)‐1β, IL‐18 and tumour necrosis factor‐α production as well as increase in IL‐10 production. Interestingly, the reduced oxidative stress status and neutrophil activation here reported were associated with rhRLX‐induced activation of endothelial nitric oxide synthase and up‐regulation of inducible nitric oxide synthase, possibly secondary to activation of Akt and the extracellular signal‐regulated protein kinase (ERK) 1/2, respectively. Thus, we report herein that rhRLX protects the kidney against I/R injury by a mechanism that involves changes in nitric oxide signalling pathway.